2021
DOI: 10.1108/sgpe-08-2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Student, academic and professional services staff perspectives of postgraduate researcher well-being and help-seeking: a mixed-methods co-designed investigation

Abstract: Purpose This study aimed to address three key gaps in existing knowledge about postgraduate researchers’ (PGRs) well-being. It investigated 1) the frequency and nature of depression, anxiety and well-being amongst PGRs, and relatedly, characteristics that convey vulnerability, 2) factors that impact PGR well-being, and 3) factors that influence help-seeking. Design/methodology/approach The mixed-methods design comprised quantitative and qualitative approaches. Using opportunity sampling, 585 PGRs registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Work by our group, which used both qualitative and quantitative cross-sectionally designed methods, examined the mental health impact of some of the pressures faced by PGR students. We found that 196 (33.4%) and 162 (27.7%) respondents experienced moderate-to-high levels of depression and anxiety, respectively (Crook et al , 2021). These findings replicate those from other studies, nationally and internationally, revealing the high levels of psychological problems present amongst doctoral students.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Work by our group, which used both qualitative and quantitative cross-sectionally designed methods, examined the mental health impact of some of the pressures faced by PGR students. We found that 196 (33.4%) and 162 (27.7%) respondents experienced moderate-to-high levels of depression and anxiety, respectively (Crook et al , 2021). These findings replicate those from other studies, nationally and internationally, revealing the high levels of psychological problems present amongst doctoral students.…”
Section: Introductionmentioning
confidence: 95%
“…Crook and co-workers reported that a third of PGR respondents identified academic challenges (e.g. managing time and other work commitments) as having the greatest negative impact on their well-being (Crook et al , 2021). Milicev and co-workers suggested this may be associated with the ways in which PGRs respond to cumulative academic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The need for meaningful training of mentors toward a cultural shift within graduate and postdoctoral education has been documented by prior researchers (Crook et al, 2021;Morris, 2021). Specifically, Crook et al (2021) identified how positive supervision experiences make a meaningful difference for postgraduate researchers, but that many supervisors have not had sufficient training.…”
Section: Suicide Prevention Through Stress Managementmentioning
confidence: 99%
“…The need for meaningful training of mentors toward a cultural shift within graduate and postdoctoral education has been documented by prior researchers (Crook et al, 2021;Morris, 2021). Specifically, Crook et al (2021) identified how positive supervision experiences make a meaningful difference for postgraduate researchers, but that many supervisors have not had sufficient training. Interventions, such as Homer et al's (2021) Researcher Toolkit, focus on fostering well-being and building connections, and offer models for implementing interventions toward institutional cultural change.…”
Section: Suicide Prevention Through Stress Managementmentioning
confidence: 99%
“…For instance, students with different research backgrounds, interests and levels of their studies can interact and learn from each other's experiences and knowledge. Furthermore, peer support groups and learning have proved to be beneficial for student researchers (Crook et al, 2021;Meschitti, 2018) as such interactions not only benefit those seeking help but also provide a sense of SGPE 14,3 fulfilment to those providing support (Jackman et al, 2023). Literature shows that peer mentoring/learning, group study and informal social events can promote collaboration and a sense of belonging, leading to increased engagement and academic success (Boud and Lee, 2005;Cahusac de Caux et al, 2017;Hradsky et al, 2022;Meschitti, 2018).…”
mentioning
confidence: 99%